Evidence-based school counseling: Making a difference with data-driven practices - Dimmitt, Carey; Carey, John C; Hatch, Trish (Corwin Press, 2007)
Measure the difference you make in students′ academic, career, and personal/social development! Aligned with the American School Counselor Association′s National Model, this authoritative guide from highly respected counselor educators and trainers gives preservice and inservice counselors the tools to identify evidence-based practices in their field and to use data in designing, implementing, and evaluating programs and interventions. With vignettes and recommendations in every chapter, this book offers skill-building guidelines for: Analyzing outcome research to inform planning Carrying out action research and building collaborative partnerships Measuring student learning and behavior change Communicating results to stakeholders, and more.